Employing the mediator elements in the aesthetics of the television image through the children’s drama - Abd Uljalil, Mohammed Akram (Journal of Humanities & Social Sciences, 2021)
Given the importance of the subject of aesthetics of the television image in children’s drama and its great impact in raising the level of artistic production of children’s drama, and the interest of most satellite channels in this type of production that simulates different age groups for children, this research comes as a scientific attempt through which the researcher seeks to become familiar with the topic of the aesthetic of the television image in Children’s drama, and its functions and all its parts in children’s dramas, including dramas, cartoons, dolls, and children’s cinema films, by analyzing scenes from different samples in order to reveal the aesthetics of the television picture and its parts and all its functions. Where the research in the first chapter reviewed the methodological framework indicating the introduction and problem of the research with an indication of the importance of the research and the extent of the need for it and its objectives, as well as identifying the definition of the search terms. Elements of cinematic language and its expressiveness and aesthetic connotations in children’s drama, while the title of the second topic was the dramatic forms directed at children, through which the research reviewed the role of digital technologies and forms of drama, and the last topic represented the aesthetic of the artistic elements in children’s drama, which was addressed through it to the directing artistic treatment and its aesthetics in Children’s drama, and the researcher came up with a set of indicators that were a tool for analyzing the research sample. Then the research reviewed the third chapter, which included the research procedures. The final chapter represented in the analysis of the research sample, through which he reached results, among which the works were distinguished by the simplicity of their events and the characters embodied in them that make the child He interacts with it being close to his reality. Among the conclusions that the aesthetic of the television picture is a means of conveying and expressing various contents through children’s drama. Based on the foregoing, the research deals with an important aspect of the creative process in producing television drama for children, through the audio-visual medium, by identifying the aesthetics of the television image in children’s drama.